Hacia una arquitectura científica : implementación del sistema constructivo Light Steel Framing (LSF) y la metodología Building Information Modeling (BIM) en construcciones de un piso, en Colombia (2017)
INTRODUCTION. The architecture formulates through a project the answer to a request of the Society; Answer that must be dynamic, with which it can be answered to later requirements of the Society. The project is the result of a collaborative work between the project stakeholders: developer, owner, designers, builder, interventor, suppliers, among others. The architect can be the person who is in charge of leading the project. Consequently, his job can not be alien to aspects such as planning, feasibility, materials, the construction system and integral design. The project should be conceived as a set of systems such as social, knowledge, environmental, urban, economic and legal, which are related and coordinated by the technical-constructive system. For this to be possible, a methodology must be implemented and when it is not appropriate, what many call the "chaos" in the project arises. OBJECTIVES. The main objective of the present investigation is to determine the feasibility of the Light Steel Framing ( hereafter referred to as LSF) construction system, assisted by the Building Information Modeling methodology (hereafter referred to as BIM), for the construction of a floor in Colombia . As secondary objectives we can mention: Explore the Architect's job as a coordinator of an interdisciplinary team that develops a collaborative activity, within a project. Create families and types in the Revit software to facilitate the implementation of the LSF. Demonstrate that materials and construction systems are not aspects of a project outside the job of Architecture. Understand the LSF, in order to be able to implement it within our environment. THEORICAL FRAMEWORK. BIM methodology by using a model, condenses in a harmonious way the information of a project.--Tomado del Formato de Documento de Grado.